Comparison of 192Os(p,n)192Ir and 192Os(d,2n)192Ir Nuclear Reactions for 192Ir Production - M. Rezki; I. Kambali; E. Hidayanto; F. Arianto (Atom Indonesia, 2020)
Iridium-192 (192Ir ) is a radionuclide currently suggested for brachyteraphy. One of the methods employed to produce high purity 192Ir is by irradiation of Osmium-192  (192Os) target using cyclotron. The success of 192Ir radionuclide production in cyclotrons requires deep understanding of irradiation parameters, including particle energy, target preparation and thickness, particle beam curent and irradiation time. Therefore, theoretical calculations of the 192Ir radioactivity yields should be carried out as a preliminary measure for more efficient 192Ir production. In this study, 192Ir production was simulated using the SRIM 2013 program to determine the optimum target thickness while the nuclearcross-section data were extracted from TENDL 2017. Two nuclear reactions for 192Ir production yield calculations were compared, i.e., 192Os(p,n)192Ir  and 192Os(d,2n)192Ir. The radioactivity yields for 192Os(p,n)192Ir nuclear reaction was found to be lower than  192Os(d,2n)192Ir reaction. For proton and deuteron energy of 30 MeV, the maximum radioactivity yield was 6.79 GBq for 192Os(p,n)192Ir and  26.14 GBq for 192Os(d,2n)192Ir. Several radionuclide impurities such as 191mIr, 190Ir, 191Os and 189Re were predicted to be generated during 192Os(p,n)192Ir reaction for proton incident energy between 1 and 30 MeV; meanwhile, 192Ir, 191mIr, 193Os, 193mIr, 192mOs and 191Os radionuclides were expected to contaminate during 192Os(d,2n)192Ir reaction for deuteron energy between 1 and 30 MeV. Results of this study can be used as a reference for future 192Ir radionuclide production when proton or deuteron beams are considered to be employed.